Potential of Bacteria Escherichia coli and Staphylococus aureus as Degradation Agent Waste Used Oil - Banjarnahor, Relina Cindy Octavia; Angraini, Dini Izza; Lestari, Ratih Dewi; Putri, Jaurani Nurul; Diyati, Rahayu; Alvi, Alvi; Putri, Selvi Heriani; Yusuf, Ashif Irvan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Oil is one of the petroleum derivatives that cause environmental pollution. Oil used in the automotive industry such as workshops is often not managed properly, so that it becomes waste that can cause soil pollution and water pollution. One way that can be used to overcome this pollution is by bioremediation by utilizing Escherichia coli and Staphylococus aureus bacteria as bioremediation agents. The purpose of this study was to determine the ability of E.coli and S.aureus bacteria in degrading oil. The method used was experimental method. The results obtained show that E.coli bacteria have the ability to degrade waste oil by bioaccumulation which is characterized by the presence of oil clots in the center of the media. While S. aureus bacteria have the ability to degrade waste oil by biodegradation which is characterized by the decomposition and change in the shape of oil oil into white granules.